Alterações morfofisiológicas em mudas de Eugenia uniflora L. E Gallesia integrifolia (Spreng.) harms após a rustificação química - Cruz, Maria Soraia Fortado Vera (2023)
Considering the economic and ecological importance of the species studied, the benefits of using quality seedlings that are acclimatized to stress conditions, as well as the need to use effective methods that provide improvements in the quality of the seedlings. This research aimed to evaluate the morphophysiological changes and water relations in Eugenia uniflora L. and Gallesia integrifolia (Spreng.) Harms seedlings, under normal growth conditions and under water restriction, after hardening with methyl jasmonate (MeJa) and potassium silicate (K2SiO3). The research was conducted from March to August 2022, in a protected cultivation environment. The experimental design used was randomized blocks, consisting of three treatments and seven blocks. The treatments consisted of applications of 100 µmol L-1 of MeJa, 5 mL L-1 of K2SiO3 and the control treatment. Subsequently, the seedlings were transplanted into pots with a capacity of three liters, filled with local soil. The results of this research were divided into three chapters. In chapter I, morphometric variables were determined to determine the seedling growth analysis. Hardening treatments provided changes in the growth dynamics of E. uniflora and G. integrifolia seedlings, promoting morphophysiological adaptations that help in tolerance to post-planting stress. In chapter II, physiological parameters were evaluated. Hardening of seedlings with K2SiO3 provided a greater increase in lignin content and greater water use efficiency, these being indicators of greater rusticity. In chapter III, morphophysiological parameters and water relations of seedlings after water deficit were evaluated. The hardening treatments promoted modulations in the water relations of the species due to the water deficit. In general, it can be concluded that the hardening methods with MeJa and K2SiO3 were effective in inducing defense responses in E. uniflora and G. integrifolia seedlings. However, it is noteworthy that new studies must be carried out with the seedlings in the field to prove the effectiveness of the products in post-planting establishment.